Melipona mandacaia: um modelo na avaliação do impacto antropogênico em abelhas, seus produtos e serviços ecossistêmicos - Souza, Isabelle Leticia Bender de (2024)
Brazilian agriculture is one of the country's main economic activities, and bees play a vital role in this context, facilitating plant pollination, which is essential for fruit and seed production, and sustaining biodiversity and the global economy. Meliponiculture, the breeding of stingless bees, is economically significant, especially for rural and indigenous communities, due to the sale of honey. However, recently there has been a marked decline in insect populations, including Melipona mandacaia, a bee species endemic to the Caatinga region, due to anthropogenic changes. This study uses biomarkers to assess the health status of Melipona mandacaia, a stingless bee native to the Caatinga biome, as indicators of anthropogenic stress. The biomarkers include cholinesterases (ChE) to assess neurotoxicity, catalase (CAT) to measure antioxidant responses, glutathione S-transferase (GST) for detoxification pathways, and lipid peroxidation (LPO) as an indicator of oxidative stress. The results reveal that ChE inhibition may be associated with higher stress levels due to human activities, while the other biomarkers showed mixed responses in the different stress level areas. This may be partially explained by beekeeping practices at some sites, which may have mitigated the effects of pesticides and fuel combustion to a certain extent. These results highlight the importance of monitoring the health of wild bees in the Caatinga. In addition to analyzing the organisms, it is also possible to investigate environmental contamination in bee products such as honey. Raman spectroscopy is an efficient technique for non-destructive, fast and accurate analysis for the chemical characterization and authentication of honey. The systematic literature review identified articles with the search term “HONEY AND RAMAN” to identify and organize Raman peaks associated with honey, analyzing articles published between 2000 and 2024. Varied wavelengths were evaluated, such as 532 nm, 785 nm and 1064 nm, resulting in the description of 411 relevant peaks. The technique showed divergences in the description of peaks between studies. For the 532 nm laser, the biggest discrepancy was in the “same molecules and different vibrational modes” category, while at 785 nm and 1064, most of the divergence was related to the “same molecules and vibrational modes” description. This difference indicates challenges such as spectral overlap and ambiguity in peak assignment. It can be concluded that Raman spectroscopy can contribute to the identification and authentication of honey, strengthening its applicability in environmental studies and product quality assurance.